(3GdEjVGMs - (3GdMSf Hf CMeO Hf YHO GdZaGQ GdaGQSqj, CHh Ydj,J (B377 (3g` s; (3CHhYHO Gddg GdfLGJj eMehO Hf YeQ GdfjSGHhQj,J (B713 (3g` s ((3YHO GdQMef Hf CMe Hf YHO Gddg Hf Ydi GdUfgGLi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf aEfi LeYJ ai gPG GdcJGH CHhGHkG ef GdYQHjI s
(3BNQgG (B:s
(3hPdc Cf GdVGO hGdTjf MJi GJUdJG HeNGQL gPg GdMQha Je cJGH GdG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YGQa MceJ HGdeOjfI GdefhQI(B((3fMh (B20) s
Keywords: (3GdfMhs